Piezoelectric Bone Surgery: A Review of the Literature and Potential Applications in Veterinary Oromaxillofacial Surgery - Hennet, Philippe (Frontiers in Veterinary Science, 2015)
Piezoelectric bone surgery is a recent and innovative technology permitting a selective cut of mineralized tissue while sparing soft tissue. Similar to a dental scaler, a high frequency vibration, in the range of 25-35kHz, is transmitted to a metallic tip. However, the power of the piezosurgical instrument is 3 to 6 times higher than that of a dental scaler. The major advantages of this technology include high precision, a design that increases ease of curvilinear osteotomy, less trauma to soft tissue, preservation of neurological and vascular structures, reduced hemorrhage, minimal thermal damage to the bone as well as overall improvement of healing. The handpiece of the instrument is equipped with a sterile irrigation system and light-emitting diode (LED) light, which improves visibility and overall safety. Piezoelectric surgery is particularly useful when performing delicate bone procedures such as periodontal or endodontic surgery. It is also indicated when performing more invasive bone surgery such as maxillectomy, mandibulectomy, and condylectomy, where preservation of neurovascular structures is important. Piezoelectric instruments are different from rotary instrumentation or oscillating saws, they require light pressure with constant motion of the tip. Training is required to master the technique.